2018
DOI: 10.1093/nar/gky032
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptome sequencing reveals extensive alternative trans-splicing and cis-backsplicing in human cells

Abstract: Transcriptionally non-co-linear (NCL) transcripts can originate from trans-splicing (trans-spliced RNA; ‘tsRNA’) or cis-backsplicing (circular RNA; ‘circRNA’). While numerous circRNAs have been detected in various species, tsRNAs remain largely uninvestigated. Here, we utilize integrative transcriptome sequencing of poly(A)- and non-poly(A)-selected RNA-seq data from diverse human cell lines to distinguish between tsRNAs and circRNAs. We identified 24,498 NCL events and found that a considerable proportion (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 89 publications
(221 reference statements)
2
92
0
Order By: Relevance
“…Finally, northern blotting is a more stringent way based on the specific probe [134]. There are also some limitations, some linear RNAs with the same sequences as those through BSJ sites may be theoretically amplified by qRT-PCR, suggesting other existing mechanisms such as trans-splicing and template switching [135,136]. Otherwise, some studies demonstrated that some abundant linear RNAs were still detected while some cir-cRNA also were digested after prolonged RNase R treatment [26,109,136].…”
Section: Research Strategies and Identificationmentioning
confidence: 99%
“…Finally, northern blotting is a more stringent way based on the specific probe [134]. There are also some limitations, some linear RNAs with the same sequences as those through BSJ sites may be theoretically amplified by qRT-PCR, suggesting other existing mechanisms such as trans-splicing and template switching [135,136]. Otherwise, some studies demonstrated that some abundant linear RNAs were still detected while some cir-cRNA also were digested after prolonged RNase R treatment [26,109,136].…”
Section: Research Strategies and Identificationmentioning
confidence: 99%
“…Alu elements are primate specific and inverted Alu elements has been reported to affect the biogenesis of trans-splicing [37]. We wondered whether inverted Alu elements may be responsible for the formation of the six human-specific chimeric RNAs including PAX3-FOXO1.…”
Section: Discussionmentioning
confidence: 99%
“…PacBio SMRT sequencing provides better completeness to the sequencing of both the 5’ and 3’ ends of cDNA molecules; thus, it is a superior strategy for the direct generation of a comprehensive transcriptome with precise AS isoforms and novel genes [3637]. Yi et al identified 33,300 full-length transcripts (transcript N50 of 5234 bp) of Misgurnus anguillicaudatus based on SMRT sequencing, and constructed a transcriptome by performing functional annotations of the non-redundant transcripts with public databases [38].…”
Section: Discussionmentioning
confidence: 99%